2014
DOI: 10.1093/brain/awu236
|View full text |Cite
|
Sign up to set email alerts
|

Diffuse white matter tract abnormalities in clinically normal ageing retired athletes with a history of sports-related concussions

Abstract: Sports-related concussions have been shown to lead to persistent subclinical anomalies of the motor and cognitive systems in young asymptomatic athletes. In advancing age, these latent alterations correlate with detectable motor and cognitive function decline. Until now, the interacting effects of concussions and the normal ageing process on white matter tract integrity remain unknown. Here we used a tract-based spatial statistical method to uncover potential white matter tissue damage in 15 retired athletes w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
109
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(123 citation statements)
references
References 96 publications
13
109
0
1
Order By: Relevance
“…2,61 The purpose of this investigation was to assess the relationships among 3 neuroimaging findings (cavum septum pellucidum, FA global mean, and microhemorrhages) and neuropsychological test performance and symptom endorsement in a relatively large sample of retired National Football League (NFL) athletes. For this initial investigation, based on the prior literature examining retired NFL players, 23,33,66,74 we accepted the hypothesis that the relationships between these neuroimaging parameters and neuropsychological test and symptom scores would be significantly associated, as evidenced by multiple statistically significant correlations.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…2,61 The purpose of this investigation was to assess the relationships among 3 neuroimaging findings (cavum septum pellucidum, FA global mean, and microhemorrhages) and neuropsychological test performance and symptom endorsement in a relatively large sample of retired National Football League (NFL) athletes. For this initial investigation, based on the prior literature examining retired NFL players, 23,33,66,74 we accepted the hypothesis that the relationships between these neuroimaging parameters and neuropsychological test and symptom scores would be significantly associated, as evidenced by multiple statistically significant correlations.…”
mentioning
confidence: 98%
“…47 Utilizing these advanced neuroimaging techniques, several studies have correlated positive neuroimaging findings (thought to result from cumulative RBT) with neurocognitive decline. 23,33,59,66,67,74 As a result, it has become widely accepted that RBT leads to structural brain pathology, which in turn can serve as either an in vivo or postmortem biomarker for clinical diagnoses of abnormal neurobehavioral changes or neurocognitive decline. However, this widely accepted paradigm warrants further study due to limitations inherent to studying RBT, including small sample sizes and the potential for selection bias.…”
mentioning
confidence: 99%
“…Additionally, preliminary analyses of diffusion tensor imaging data on this sample indicate reduced fractional anisotropy in the mTBI group in the right genu/body of the corpus callosum, bilateral internal capsule, bilateral superior longitudinal fasciculus, and bilateral infero-frontal longitudinal fasciculus (Terry and Miller 2016). Other groups examining the long-term effects of sports-related concussions have also showed differences in white matter (Hart et al 2013;Tremblay et al 2014) as well as electrophysiology, potentially in the fronto-parietal networks (Broglio et al 2012;De Beaumont et al 2009; for review, see Henry et al 2016). Taken together, there may be some neuroanatomical abnormalities in these participants, but they have not yet reached the level of gross brain atrophy or functional impairments in everyday life.…”
Section: Discussionmentioning
confidence: 72%
“…Former college athletes ages 50-75 who experienced between one and five concussions (average = 2.08) before their mid-20s showed cortical thinning in various areas, lateral ventricular enlargement, and worse memory performance when compared to their nonconcussed teammates (Tremblay et al 2013). Similar cohorts of middle-aged former athletes with remote concussions have also been showed to have differences in event-related potentials (Broglio et al 2012;De Beaumont et al 2009) and white matter integrity (Hart et al 2013;Tremblay et al 2014;see Henry et al 2016 for review). These findings resemble patterns of abnormal aging reflected in neurodegenerative conditions often seen later in life.…”
Section: Submitted As An Original Report To the Brain Imaging And Behmentioning
confidence: 99%
“…In the acute stage, the findings may be reflecting edema and axonal swelling with elevated FA due to restricted diffusion, while in the chronic phase, membrane degradation and cell lysis may permit more free diffusion and low FA [123,124]. Studies have shown acute and chronic white matter damage correlating with impaired function after TBI [118,122,[125][126][127][128]. Murugavel found increased radial diffusivity in concussed athletes.…”
Section: Diffusion Tensor Imagingmentioning
confidence: 99%